The corrosion resistance of heat-resistant alloys for parts of power equipment - Vahrusheva, V. S.; Hlushkova, D. B.; Volchuk, V. M.; Nosova, T. V.; Mamhur, S. I.; Tsokur, N. I.; Bagrov, V. A.; Demchenko, S. V.; Ryzhkov, Yu. V.; Scrypnikov, V. O.; Вахрушева, В. С.; Глушкова, Д. Б.; et al. (Харківський національний автомобільно-дорожній університет, 2022)
For the manufacture of parts and assemblies of the turbopump unit of details of power equipment, welded joints with corrosion resistant steels and heat-resistant alloys are used, requiring various modes heat treatment to achieve the required level of mechanical properties. In the manufacture of parts and assemblies of details of power equipment at the machine-building enterprises of Ukraine, it became necessary to replace semi-finished products. It is necessary to replace sheet products from high-alloy alloys ХН67МВТЮ and 06Х15Н6МВФБ with one alloy with a high complex of physical and mechanical characteristics. In the work, as a replacement for the applied heat-resistant alloys, Inconel 718 alloy welded to 316L steel. Samples of welded joints, processed according to the recommended mode, showed increased corrosion resistance.
Корозійна стійкость жароміцних сплавів для деталей енергетичного обладнання
Keywords: heat-resistant alloy; heat treatment; corrosion resistance; жароміцний сплав; термічна обробка; корозійна стійкість; 620.175.2:669.15